ECONOMIC TYPOLOGY APPROACH TO CALCULATE UNEMPLOYMENT INDEX AND REGIONAL POVERTY RATE (STUDY IN TAPAL KUDA AREA OF EAST JAVA) - Sulistyono, Setyo Wahyu (Jurnal Ekonomi Pembangunan, 2018)
The aims of this study is determining the level of unemployment index then linking the calculation of the unemployment and poverty index through mapping the economic typology, so in the end determining the form of government intervention on the solution of rigidity in the labor market and its relation to poverty in the residency area. The location of research is the area of East Java that called "Tapal Kuda". The research method used was a descriptive quantitative analysis of the location typology mapping by strengthening the results of calculation of index numbers and poverty. The results of the study reveal that the unemployment index for the majority of Tapal Kuda areas is said to be bad and has high poverty rates. This is inversely proportional to the potential of the Tapal Kuda area as a gateway for the distribution of goods and services, through an analytical approach, the availability of local community access to the economy is minimal, the lack of strengthening a community-based economy, the labor market is rigid, and wages are absorbed in the society with formal employment. The form of government policy recommendations is expected to strengthen the economy of society through local wisdom, bipartite strengthening between the government and companies with flexible wages. Reducing the amount of poverty can be done by stimulating wage policies, aligning the informal sector, strengthening MSMEs, reducing the consumption pattern of luxury goods, increasing per capita income through employment and increasing non-physical investment.